Metadiscourse in Linguistics Master’s Theses in English L1 and L2 - Burneikaitė, Nida (Kalbotyra, 2008)
Recent investigations of academic discourse have revealed considerable variations in the interpersonal uses of language: academic texts representing different genres, disciplines and languages/cultures show differences in the ways writers create interaction in text. Studies of English native (L1) and non-native/interlanguage (L2) texts have also shown variability in the use of interpersonal strategies. Many contrastive studies favour the Research Article genre, whereas other genres seem to be under-investigated. This paper focuses on the Master’s Thesis genre in the discipline of Linguistics1 in different cultural/educational contexts: British and Lithuanian universities. It describes patterns of metadiscourse in the MA thesis genre; it compares metadiscourse strategies in English texts by L1 and L2 writers; it considers the role of institutional practices and individual writer style in the way writers manage their discourse.